Factors Determining the Adoption of Induction Stove for Household Cooking in Bhaktapur - Bajracharya, Yogesh; Adhikari, Pujan; Sharma, Bishnu Prasad (Journal of Science and Engineering, 2023)
The current global warming trend is unequivocally the result of human activities and is proceeding at an unprecedented rate over the millennia. About 6.7 percent of global greenhouse gas emissions are caused by household cooking. It is essential to expand the use of clean fuels and technologies to reduce household emissions. Most households in urban areas use LPG for cooking purposes along with a gradual introduction of electric induction stoves. The main objective of this paper is to identify the factors determining the choice of induction stoves for household cooking. Primary data were collected from 300 households of Bhaktapur and Madhyapur Thimi Municipalities in March, 2021. Binomial Logit regression was performed to examine the determinant of induction stove adoption by household. LPG is the primary source of cooking for household. Sixty seven percent of households use electricity partially for cooking purposes. Forty five percent of total households use an electric rice cooker and 27 percent use an induction stove. Twenty six percent of households do not know about induction stoves. The family's education level, particularly the cooking member, is the primary determinant of adopting an induction stove. The probability of adoption of induction stoves increases with an increase in income. Families living in their own houses are more likely to use induction stoves than those living in rented houses.